Students’ Perceptions of Job-Oriented Training Programs at the University of Toliara - Hatimo Henintsoa Samira; Razafiharimbola Larissa; Hangivola Emyblonde Ratna (The Nexus Journal of Education, Management, and Entrepreneurship, 2026)
This study aims to examine students’ perceptions of job-oriented training programs at the University of Toliara, with particular attention to their relevance to labor market needs, their contribution to skill development, their influence on career awareness, and the perceived effectiveness of institutional support. By focusing on students’ viewpoints, the study seeks to provide insights into how learners experience job-oriented training and how it supports their preparation for professional life. A qualitative approach was adopted to capture in-depth perspectives and lived experiences of students. Data were collected through direct observation of training-related activities and semi-structured interviews. A total of 20 students enrolled in programs within the Department of Law, Economy, Management and Sociology (DEGS) participated in the interviews. This methodological approach allowed for a detailed exploration of perceptions, supported by observations of learning contexts and student engagement. The findings indicate that students generally perceive job-oriented training as a valuable component of their academic experience, particularly in enhancing practical skills, professional confidence, and understanding of workplace expectations. Students acknowledged the role of training in improving career awareness and helping them reflect on future professional pathways. At the same time, challenges were identified, including concerns about alignment with labor market realities, continuity of training activities, and institutional resources, which influenced perceptions of overall effectiveness. This study offers original insights by centering students’ perceptions of job-oriented training at a public university in Madagascar. This setting remains underrepresented in the higher education literature. The findings offer practical implications for institutional improvement and provide a foundation for future studies on employability-oriented training in similar contexts.